The Mediating Role of Sustainability Reporting on CSR, Dividend Policy, Profitability, Firm Size and Firm Value: Peran Mediasi Pelaporan Keberlanjutan terhadap CSR, Kebijakan Dividen, Profitabilitas, Ukuran Perusahaan, dan Nilai Perusahaan - Irma Sari Permata; Mulyadi; M. Nuruddin Subhan (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines the effects of Corporate Social Responsibility (CSR), Dividend Policy (DPR), Profitability (ROA), and Firm Size (SIZE) on Firm Value (Tobin’s Q), with Sustainability Reporting (SR) as a mediating variable in manufacturing companies in Indonesia. This study employs a quantitative approach using secondary data obtained from the annual reports of manufacturing firms listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. Multiple regression and path analyses were conducted to test both the direct and indirect relationships among the variables. The findings reveal that CSR, Dividend Policy, and Profitability significantly influence Firm Value, both directly and indirectly through sustainability reporting. Additionally, sustainability reporting is proven to partially mediate the association between these determinants and Firm Value, demonstrating that transparency in sustainability disclosure enhances corporate reputation and investor confidence. This study contributes to the body of literature on corporate sustainability by emphasizing the strategic role of sustainability reporting in optimizing firm value within emerging market settings.